Achieving climate justice: addressing disparities and enhancing equity in global climate policies - Ayompe, Lacour M. (Frontiers in Sustainable Energy Policy, 2025)
This paper interrogates the nexus between climate justice and policy-driven equity, placing a spotlight on the disproportionate vulnerabilities faced by marginalized groups, including women, Indigenous peoples, and low-income communities, in the global climate arena. It argues for incorporating diverse perspectives in decision-making processes and shows how historical injustices, particularly those rooted in colonial legacies, continue to shape current climate governance structures. Using illustrative examples, the manuscript demonstrates how local initiatives that prioritize community engagement and empowerment can effectively tailor climate strategies to address the specific needs of impacted populations. Moreover, it emphasizes the critical role of interdisciplinary collaboration, spanning public health, urban planning, and environmental protection, in crafting climate policies that mitigate environmental impacts while promoting social justice. Ultimately, this study offers practical insights and strategies for policymakers, researchers, and advocates committed to building resilient and inclusive climate policies, underscoring that embedding equity in global climate action is essential for achieving a sustainable and just future for all communities.